Attitudes and behaviors related to the introduction of electronic health records among Austrian and German citizens - Hörbst, Alexander; Kohl, Christian Dominik; Knaup-Gregori, Petra; Ammenwerth, Elske (International journal of medical informatics, 2010)
Background - Acceptance by citizens seems to be crucial for the future success of an electronic health record (EHR) in Germany and Austria. We analyzed citizens’ knowledge and expectations about the concept and contents of an EHR. We also addressed possible fears and barriers, and we investigated desired EHR functionalities relevant to citizens in the Austrian and German population. - Methods - Standardized interviews of a convenience sample of 203 Austrian and 293 German citizens recruited in two metropolises. - Results - Up to three-quarter of the interviewed citizens already collect and store medical documents at home, mostly in paper-based form. No respondents had already used an Internet-based personal health record. Between 80% and 90% of respondents were supportive of the idea of an electronic exchange of health-related data between health care providers as core functionality of an EHR. However, many respondents formulated concerns with regard to data protection and data security within an EHR. The EHR functionalities most supported by respondents included the electronic vaccination record, online information on doctors and hospitals, and the administration of appointments and reminders. - Conclusion - The results indicate a generally positive attitude towards the EHR. However, the study shows that data protection is an issue for many citizens, and that despite strong media discussion, there are information deficits with regard to the national EHR initiatives.
Gesehen am 06.03.2023